2016
DOI: 10.1016/j.brainres.2015.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin-induced neuronal degeneration in the hippocampus after neonatal intraventricular hemorrhage

Abstract: Neuronal degeneration following neonatal intraventricular hemorrhage (IVH) is incompletely understood. Understanding the mechanisms of degeneration and cell loss may point toward specific treatments to limit injury. We evaluated the role of hemoglobin (Hb) in cell death after intraventricular injection in neonatal rats. Hb was injected into the right lateral ventricle of post-natal day 7 rats. Rats exposed to anesthesia were used for controls. The CA-1 region of the hippocampus was analyzed via immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 44 publications
(46 reference statements)
12
61
0
Order By: Relevance
“…3). Deferoxamine, a potent free iron chelator, has been shown to attenuate hippocampal cell loss following IVH [39]. Of further interest, it was recently shown that deletion of Hpx, a natural hemescavenger, leads to aggravated brain injury following intracranial bleeding and increased iron deposition [40].…”
Section: Scavenger Studies Of Hb-metabolites Display the Importance Omentioning
confidence: 99%
“…3). Deferoxamine, a potent free iron chelator, has been shown to attenuate hippocampal cell loss following IVH [39]. Of further interest, it was recently shown that deletion of Hpx, a natural hemescavenger, leads to aggravated brain injury following intracranial bleeding and increased iron deposition [40].…”
Section: Scavenger Studies Of Hb-metabolites Display the Importance Omentioning
confidence: 99%
“…However, several recent studies have reported evidence of CD163 + neurons following hemorrhage. Our lab documented the first finding of CD163 expression in neurons [2,4]. A neonatal rat model was used to simulate intraventricular hemorrhage, after which CD163 was found in hippocampal pyramidal neurons.…”
Section: Cd163 In Neurons After Ichmentioning
confidence: 99%
“…When not bound to O 2 , heme-bound iron exists in a ferrous (Fe 2+ ) state capable of performing radical chemistry to create dangerous reactive oxygen species. Several studies have highlighted the hemoglobin-induced damage caused to neuronal populations during hemorrhagic stroke, suggesting the existence of pathways by which hemoglobin-associated iron can enter neurons and inflict oxidative injury [1][2][3]. While there are several known mechanisms by which free iron and heme can enter cells, the number of known hemoglobin uptake mechanisms is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleed may become severe enough to occupy >50% of the ventricle producing dilation of the ventricles (Grade III). Large IVHs are associated with unfavorable neurological outcomes (Alderliesten et al 2013, Noori et al 2014, Garton et al 2016). Adverse neurodevelopmental sequelae include cerebral palsy, seizures, and hydrocephalus requiring a shunt, blindness, deafness, and cognitive impairment (Goldenberg and Jobe 2001, Hintz and O’Shea 2008).…”
Section: Introductionmentioning
confidence: 99%